2002
DOI: 10.1074/jbc.m202765200
|View full text |Cite
|
Sign up to set email alerts
|

The Requirement of H1 Histones for a Heterodimeric Nuclear Import Receptor

Abstract: After synthesis in the cytoplasm, H1 histones are imported into the nucleus through an energy-dependent process that can be mediated by an importin ␤-importin 7 (Imp␤-Imp7) heterodimer. H1 histones contain two structurally different types of nuclear localization signals (NLS). The first type of NLS resides within the unstructured C-terminal domain and is rich in basic amino acids. In contrast, the highly conserved central domain of the H1 histone contains comparatively few basic amino acids but also represents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
52
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 37 publications
5
52
2
1
Order By: Relevance
“…Previous studies revealed the Imp␤⅐Imp7 heterodimer to be the only functional import receptor for H1 linker histones (12,13). The binding sites on Imp␤ for Imp7 and H1 0 have already been identified (12) and include HEAT repeats 4 -9 (Imp7) and HEAT repeats 6 -19 (H1 0 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies revealed the Imp␤⅐Imp7 heterodimer to be the only functional import receptor for H1 linker histones (12,13). The binding sites on Imp␤ for Imp7 and H1 0 have already been identified (12) and include HEAT repeats 4 -9 (Imp7) and HEAT repeats 6 -19 (H1 0 ).…”
Section: Resultsmentioning
confidence: 99%
“…In Vitro Nuclear Import Assays and Immunofluorescence Detection-Preparation of the fluorescent import substrates 4z-rpL23a and 6z-H1 0 was done as described (10,13). The permeabilization of HeLa cells, the preparation of the energy regenerating system, and the Ran mix were done according to the protocol of Adam et al (18) and modifications described by Jäkel and Görlich (10).…”
Section: Recombinant Protein Expression and Protein Purification-mentioning
confidence: 99%
See 3 more Smart Citations